Postoperative outcome of deviated nasal septum and its effect on quality of life - Siddique, Mohsina; Mili, Mohan Kumar; Borah, Pronami; Jayan, Laya K. (International Journal of Research in Medical Sciences, 2025)
Background: Deviated nasal septum (DNS) is a common clinical entity. The most common complaint is nasal obstruction followed by headache, facial pain, nasal discharge. All these symptoms lead to reduced physical and emotional wellbeing with poor quality of life. Nasal septal surgery is strongly indicated in these patients which not only lead to improvement of symptoms but also improved quality of life. Sinonasal Obstruction Test (SNOT) 22 is a questionnaire which helps in selecting patients preoperatively and also helpful in postoperative assessment of symptoms. The aim of the study is to assess quality of life in patients following DNS surgeries using SNOT 22 questionnaire in patients admitted in department of ENT in a tertiary care hospital. Methods: Hospital based prospective observational study with 50 patients who presented to Department of Otorhinolaryngology, Assam Medical College and Hospital, with DNS and having symptoms. Results: Highest incidence was seen in 21-30 years. There were 58% male and 42% female. Most common symptom was nasal obstruction (92%). Right sided DNS is more common (60%). SMR was done in 44% patients while Septoplasty in 56%. Postoperative SNOT 22 scores showed significant improvement in all 22 symptoms with highest improvement in nasal blockage and headache. Also, quality-of-life (QoL) related symptoms showed significant improvement following surgery. Conclusions: Septal surgeries in symptomatic patients showed improvement in symptoms including quality of life with the help of SNOT 22 questionnaire.